2009
DOI: 10.4314/thrb.v11i2.45208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined use of Mosquito Magnet Liberty Plus™ trap and insecticide treated net on human biting rates of Anopheles gambiae s.s. and Culex quinquefasciatus

Abstract: Malaria is the most important public health problem in Sub-Saharan Africa. There is a pressing need for development and use of alternative control approaches, which will remain effective even with increasing threat of mosquito resistance to chemical control and smaller number of approved chemical insecticides. This study evaluated the effect of combined use of attractant baited Mosquito Magnet Liberty Plus™ (MM) trap and bed nets on human mosquito biting rates under semi-field conditions. Human landing catch d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(7 reference statements)
0
6
0
1
Order By: Relevance
“…The advantage of the MM-Plus over the CDC light trap and the BG-Sentinel trap is its functional longevity. It can function for weeks without needing new batteries or additional propane and may in time even be used as a tool in the integrated mosquito control rather than for mosquito monitoring (Kitau et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the MM-Plus over the CDC light trap and the BG-Sentinel trap is its functional longevity. It can function for weeks without needing new batteries or additional propane and may in time even be used as a tool in the integrated mosquito control rather than for mosquito monitoring (Kitau et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Some contemporary models of Mosquito Magnet ® use CO 2 + octenol as a synergic attractant ( Takken & Kline 1989 , Kline et al 1991 ). The advantage of the Mosquito Magnet ® over the CDC light trap and the BG-Sentinel ® is its functional longevity because it can function for weeks without batteries or propane replacement ( Davis et al 1995 , Schmied et al 2008 , Kitau et al 2009 ).…”
mentioning
confidence: 99%
“…Although it has been shown that the traps can be used for mosquito control and routine surveillance, the MM traps are marketed for the control of blood-seeking insects in residential areas (mosquitomagnet.com), although the traps have shown that can be used for mosquito control and routine surveillance (Pucci et al 2003, Brown et al 2008, Xu et al 2008, Kitau et al 2009. The MM trap is battery operated and utilises CO 2 , one of the products of the catalysis of propane gas, as an attractant (Kline 1999).…”
mentioning
confidence: 99%
“…The MM trap is battery operated and utilises CO 2 , one of the products of the catalysis of propane gas, as an attractant (Kline 1999). In addition, other attractants, such as octenol and L-lactic acid, have been evaluated (Pucci et al 2003, Cileck & Hallmon 2005, Kitau et al 2009, Dusfour et al 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation